The lipid digestion behavior of oil-in-water Pickering emulsions stabilized by whey protein microgels of various rigidities. (September 2022) - Chen, Shanan; Du, Yizheng; Zhang, Huijuan; Wang, Qimeng; Gong, Yifu; Chang, Ruxin; Zhang, Jiayin; Zhang, Jipeng; Yuan, Yu; Liu, Bin; Yan, Huiling; Li, Yuan
Abstract: Pickering emulsion stabilized by whey protein microgels (WPMs) possesses a retarded lipid digestion property may reduce the calorie intake. However, the rigidity of WPMs on emulsion stability and lipid digestion has not been investigated systematically. Herein, the WPMs with various rigidities made of 5%, 10% and 20% (w/w) whey protein isolate (WPI) were prepared. Atomic Force Microscopy characterization suggested that higher WPI concentration led to a larger young's modulus of microgel particles. The interfacial properties of the particles absorbed at the water-oil interface revealed that the soft microgel particles (5%) showed excellent deformability compared with the harder ones (10% and 20%). Besides, softer particles also exhibited faster interfacial adsorption rates, higher interfacial coverage and superior ability in reducing interfacial tension. Then those WPMs were applied to prepare oil-in-water Pickering emulsions. The soft WPMs stabilized Pickering emulsion showed the optimum colloidal stability. Furthermore, WPMs stabilized Pickering emulsions showed a delayed lipid digestion rate, thus the soft WPMs stabilized high internal phase Pickering emulsion was applied as a healthier margarine substitute. This work provides an inspiration for WPMs Pickering emulsions in reduced calorie intake food design. Graphical abstract: Image 1 Highlights: Whey protein microgels with various rigidities were prepared by heat cross-linking. Soft WPMs had excellent interfacial viscoelastic and absorption properties. Soft WPMs-PE had the optimum colloidal stability. WPMs-PEs built interfacial barriers and delayed lipid digestion rate effectively. WPMs-HIPPE can be the potential healthier substitute to margarine.